Influence of Profitability and Solvency Ratios on Price-to-Book Value of Banking Companies Listed in the LQ45 Index (2020–2024) - Dean Rezaldi Agustianto; Rina Maria Hendriyani (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This research investigates the impact of Profitability, measured by Return on Assets (ROA), and Solvency, measured by Debt to Equity Ratio (DER), on the Price to Book Value (PBV) of banking firms within the LQ45 index. The study seeks to evaluate how these core financial indicators shaped market valuations during the post-pandemic recovery period spanning 2020 to 2024. Methodology: Utilising a quantitative framework, the study applies multiple linear regression to analyse financial data from the specified period. The analysis focuses on both simultaneous and partial effects of the independent variables on market value, ensuring the statistical integrity of the findings through standard diagnostic procedures. Results: The F-test shows that ROA and DER collectively affect PBV. However, the t-test reveals that DER has a significant negative effect, while ROA has no significant effect on PBV. The Adjusted R-Square is 0.435. Findings:  Findings from the F-test indicate that ROA and DER collectively influence PBV. However, individual t-tests demonstrate a significant negative correlation between DER and PBV, while ROA appears to have no substantial effect during this period. The model achieves an Adjusted R-Square of 0.435. Novelty: The results suggest that 43.5% of the variation in PBV can be explained by the selected variables. Notably, the data implies that during this recovery phase, investors in the banking sector prioritised debt levels and solvency over immediate profitability as a benchmark for market valuation. Originality: This study contributes to the literature by examining the specific economic transition between 2020 and 2024. It highlights how market dynamics in the high-cap banking sector shifted in response to the unique financial pressures of the post-pandemic era. Conclusion: olvency emerges as a primary determinant of market value for LQ45 banks, whereas the influence of profitability remained limited. These insights suggest that in volatile recovery markets, investors tend to scrutinise debt management more closely than traditional earnings metrics when evaluating banking stocks. Type of Paper: This paper is an empirical research paper.